Parametric estimation for indoor localization application - Hairul bin Anuwar (2016)
This report shows the parametric estimation of Line-of-Sight (LOS) and Non Line-of-Sight (NLOS) paths for localization. The parametric estimation of the LOS and NLOS paths like Time of Arrival (TOA) and Angle of Arrival (AOA) using Space-Alternating Generalized Expectation (SAGE) algorithm are explained. The experiment set up and execution will then be shared. Subsequently, the data obtained from the experiment will be processed using MATLAB software to produce the estimated TOA and AOA. With the estimated TOA and AOA found, the LOS and NLOS path can be known and used for localization. The errors of the measured values were then compared to the actual values to evaluate the accuracy of the parameter estimation. The errors of localization using LOS and NLOS will also be shown. Lastly are the future works that can be implemented to achieve better parameter estimation for localization.